2019
DOI: 10.21203/rs.2.382/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Call for Consensus in Defining Efficacy in Clinical Trials for Opioid Addiction: Combined Results from a Systematic Review and Qualitative Study in Patients Receiving Pharmacological Assisted Therapy for Opioid Use Disorder

Abstract: Background Given the complex nature of opioid addiction treatment and the rising number of available opioid substitution and antagonist therapies (OSAT), there is no ‘gold standard’ measure of treatment effectiveness, and each successive trial measures a different set of outcomes which reflect success in arbitrary or opportune terms.We sought to describe the variation in current outcomes employed across clinical trials for opioid addiction, as well as determine whether a discrepancy exists between the treatmen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Presently, several pre‐clinical studies are being performed using miRNAs as biomarkers or therapeutics for diseases, but no clinical trials, and few pre‐clinical trials, exist specifically for addiction (Creed, 2018; Dennis et al, 2020; Edemann‐Callesen, Barak, Hadar, & Winter, 2020; Whyte, Torregrossa, Barker, & Gourley, 2018). Many drug abuse studies rely on self‐reported data, and reliable diagnostics are difficult and expensive (Nora D. Volkow, Koob, & Baler, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Presently, several pre‐clinical studies are being performed using miRNAs as biomarkers or therapeutics for diseases, but no clinical trials, and few pre‐clinical trials, exist specifically for addiction (Creed, 2018; Dennis et al, 2020; Edemann‐Callesen, Barak, Hadar, & Winter, 2020; Whyte, Torregrossa, Barker, & Gourley, 2018). Many drug abuse studies rely on self‐reported data, and reliable diagnostics are difficult and expensive (Nora D. Volkow, Koob, & Baler, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes will be coded as being patient important or not, as what was previously defined among a substance use population. 27 For the purpose of evidence mapping, data will be grouped according to outcome, prognostic factors and whether outcomes selected were patient-important.…”
Section: Methodsmentioning
confidence: 99%